KONTRIBUSI SEKTOR PERIKANAN DALAM PEREKONOMIAN KABUPATEN MALUKU TENGAH - Meitha M Kaihatu (Jurnal Matematika Sains dan Teknologi, 2018)
Maluku Tengah District have the potential fisheries resources. But the contribution of fishery against Gross Regional Domestic Product (GRDP) only of 6.20%. In general, this research aims to identify and analyze the contribution of fisheries sector in the economy of the Maluku Tengah district, knowing the level of the base, and analyze the fishery economic typology. The methods used are secondary data analysis. Data analysis is an analysis of Shift Share analysis, Location Quotient (LQ), and analysis of the Klassen Typology. The calculation of the value of the contribution, the value of LQ, typology of economic sector of fisheries in Maluku Tengah district obtained the results that the contribution of fishery on the basis of prevailing prices and constant prices put the fishery on the order/rank fifth and sixth in the achieving of GRDP, the sector of fisheries in Maluku Tengah district is not a sector basis with patterns and economic structures that are growing but are at a condition relative's left behind. There are five sub-districts that became a priority and need to be developed/improved, among others: Banda, Tehoru, Salahutu, Leihitu, and Seram Utara. Kabupaten Maluku Tengah memiliki potensi sumberdaya perikanan yang cukup besar. Namun sumbangan sektor perikanan terhadap Produk Domestik Regional Bruto (PDRB) hanya sebesar 6,20%. Secara umum penelitian ini bertujuan untuk mengidentifikasi dan menganalisis kontribusi sektor perikanan dalam perekonomian wilayah Kabupaten Maluku Tengah, mengetahui tingkat basis, menganalisis tipologi ekonomi sektor perikanan.Metode yang digunakan adalah analisis data sekunder. Analisis data yang digunakan adalah analisis Shift Share, analisis Location Quotient (LQ), dan Analisis Tipologi Klassen. Perhitungan nilai kontribusi, nilai LQ, tipologi ekonomi sektor perikanan di Kabupaten Maluku Tengah diperoleh hasil bahwa kontribusi sektor perikanan atas dasar harga berlaku dan harga konstan menempatkan sektor perikanan pada urutan/peringkat kelima dan keenam dalam pembentukan PDRB, sektor perikanan di Kabupaten Maluku Tengah bukan merupakan sektor basis dengan pola dan struktur ekonomi yang sedang bertumbuh namun berada pada kondisi relatif tertinggal. Terdapat lima kecamatan yang menjadi prioritas dan perlu dikembangkan/ditingkatkan antara lain: Banda, Tehoru, Salahutu, Leihitu, dan Seram Utara.